Case Report: Atypical Solitary Brain Metastasis: The Role of MR Spectroscopy In Differential Diagnosis - Kozic, Dusko; Lasica, Nebojsa; Grujicic, Danica; Raicevic, Savo; Prvulovic Bunovic, Natasa; Nosek, Igor; Boban, Jasmina (Frontiers in Oncology, 2022)
Background Metastatic brain tumors are typically located at the cerebral hemispheres or the cerebellum and most frequently originate from primary breast or lung tumors. Metastatic lesions are usually associated with blood–brain barrier disruption, solid or ring-like contrast enhancement, and perilesional vasogenic edema on brain imaging. Even in cases where metastases are predominantly cystic, enhancement of the minor solid component can be detected. In contrast, non-enhancing secondary brain tumors were only reported in a patient after antiangiogenic treatment with bevacizumab. Case report We report a case of a 54-year-old male who presented with left-sided weakness and multiple seizures. Brain magnetic resonance imaging revealed a T2-weighted heterogeneous solid tumor in the right frontoparietal parasagittal region, with no apparent enhancement on T1-weighted post-contrast images and no evident perilesional edema. Further MRS analysis revealed markedly increased choline and lipid peaks. The patient underwent craniotomy for tumor removal. Histopathology revealed findings consistent with metastatic non-microcellular neuroendocrine lung cancer. positron emission tomography/computed tomography (PET/CT) revealed a stellate lesion within the right upper lung lobe, compatible with primary lung cancer. Conclusion Non-enhancing brain metastatic tumors are rarely reported in the literature, usually following antiangiogenic treatment. Here, we report the first ever case of a non-enhancing metastatic brain tumor with no prior history of antiangiogenic treatment, with particular emphasis on the importance of MRS analysis in atypical brain lesions.